Internalisasi Nilai-nilai Pendidikan Multikultural dalam Pembelajaran Fikih pada MTs DDI Kaballangang Kabupaten Pinrang - St. Wardah Hanafie Das; Abdul Wahab (Madrasah Tsanawiyah DDI Cilellang, 2021)
This study aims to (1) determine the dimensions of multicultural values in fiqh learning at MTs DDI Kaballangang, Pinrang Regency; (2) describe the process of internalizing multicultural values in fiqh learning at MTs DDI Kaballangang, Pinrang Regency; and (3) analyzing the results of internalizing multicultural values in fiqh learning at MTs DDI Kaballangang, Pinrang Regency. The type of research is qualitative with pedagogical, psychological, and philosophical approaches. The data source consisted of documents and resource persons from the leaders and Fiqh teachers of MTs DDI Kaballangang, Pinrang Regency. Data collection techniques through observation, documentation, and interviews. Data analysis techniques through data reduction, data display, and conclusions drawing. The results showed that the dimensions of multicultural values in fiqh learning in MTs DDI Kaballangang were tolerance values, equality rights, brotherhood values, justice values, and social ethical values. The process of internalizing multicultural values in fiqh learning at MTs DDI Kaballangang by promoting values of tolerance and not fanatical, being inclusive, not discriminating, teaching the background of the emergence of differences, ethics in addressing differences, and prioritizing the values of peace and unity. Internalization of multicultural values in fiqh learning at MTs DDI Kaballangang has implications for the development of three areas of student competency: 1) Attitudes, namely cultural awareness and sensitivity, and responsiveness to culture; (2) knowledge, namely knowledge about the language and culture of others, the ability to analyze and translate cultural behavior, and knowledge of cultural awareness; and (3) skills, namely skills to avoid conflict and the ability to correct distortions, stereotypes, and misconceptions about ethnic groups.